Two ways:
1) guess factors(trial and error)
2) use quadratic formula.
If you use this method then a = -3, b = -6 and c = -1
x = -b +/- [sqrt(b^2 -4ac)/2a]
substituting a, b, and c into our equation we get:
x = - (-6)+/- [sqrt ((-6)^2) - 4(-3)(-1))/2 (-3)]
x = + 6 +/- [sqrt (36 -4 (3)/-6)] if I didnt make a mistake in my signs
x = + 6 +/- [sqrt (36 -12)/-6)]
x = 6 +/- [sqrt (24)/-6] but sqrt 6 x sqrt of 4 = sqrt 24 hence
x = 6 +/- [ sqrt 6 x sqrt 4 /-6] that is:
x = 6 +/- [sqrt 6 x 2 /-6 ]
so x = 6 + [sqrt 6 x 2/-6] and x = 6 - [sqrt 6 x 2/-6]
M∠X= m∠Q Therefore the m∠X= 47°
It’s 34. hope this helps xx
Answer:
12=d
Step-by-step explanation:
correct answer :)
Answer:
g+192=354
Step-by-step explanation:
g and 192 MORE, the more tells you that you are adding 192 to g. and it is saying that g+192=354.